Pemetaan jalur pendakian Gunung Lawu via Babar berbasis Sistem Informasi Geografis (SIG) sebagai upaya mendukung wisata minat khusus - Hidayat, Septian Nur; Wirahayu, Yuswanti Ariani; Astina, I Komang; Insani, Nailul (Jurnal Praksis dan Dedikasi Sosial, 2025)
Mapping the Mount Lawu hiking trail via Babar using a Geographic Information System (GIS) to support special interest tourism The popularity of Mount Lawu hiking as a special interest tourism has increased. Mount Lawu is a popular destination for hikers because of its natural beauty, history, and culture. Popular hiking trails are via Candi Cetho and via Cemoro Sewu. However, in 2019, a new alternative hiking trail was available, namely the Babar hiking trail, managed by the Wono Tirto Forest Village Community Organization (LMDH). The Babar hiking trail has the advantage of a lower slope than other trails, and there are several relic sites of the Majapahit kingdom along the hiking trail. The Babar hiking trail has not had an appropriate map of the hiking trail since its opening. This research aims to produce a Geographic Information System (GIS)-based digital map that provides information on special interest tourism hiking trails (Mount Lawu hiking) in supporting mountaineering management. The method used in this research is Participatory GIS (P-GIS) with an LMDH officer. Data was collected through ground surveys with the Avenza Maps application, and analyzed using Quantum Geographic Information System (QGIS) to produce digital maps. The resulting hiking trail map is equipped with necessary information, including Basecamp, post, shelter, water point, site point along the trail, peak, distance, and estimated travel time. The map can be accessed offline for navigation and location tracking. This digital map makes it easier for hikers to navigate and plan, reducing the risk of accidents during mountain hiking activities. Popularitas wisata minat khusus pendakian Gunung Lawu mengalami peningkatan. Gunung Lawu merupakan destinasi populer bagi pendaki berkat keindahan alam, sejarah, dan budaya. Jalur pendakian yang terkenal antara lain Jalur Pendakian Gunung Lawu via Candi Cetho dan via Cemoro Sewu, namun pada tahun 2019 tersedia jalur pendakian alternatif baru yaitu jalur pendakian via Babar yang dikelola oleh Lembaga Masyarakat Desa Hutan (LMDH) Wono Tirto. Jalur pendakian via Babar memiliki keunggulan yaitu kemiringan lereng lebih rendah dibandingkan jalur lain dan terdapat beberapa situs peninggalan kerajaan majapahit di sepanjang jalur pendakian. Jalur Pendakian Babar belum memiliki peta jalur pendakian yang memadai sejak dibuka. Penelitian ini bertujuan menghasilkan peta digital berbasis Sistem Informasi Geografis (SIG) yang memiliki manfaat untuk menyediakan informasi jalur pendakian wisata minat khusus (pendakian Gunung Lawu) dalam mendukung manajemen pendakian gunung. Metode yang digunakan dalam penelitian ini adalah survey dengan implementasi SIG Partisipatif (SIG-P) bersama pengurus LMDH Wono Tirto. Data dikumpulkan melalui survei lapangan dengan aplikasi Avenza Maps, dan dianalisis menggunakan Quantum Geographic Information System (QGIS) untuk menghasilkan peta digital. Peta jalur pendakian yang dihasilkan dilengkapi dengan informasi penting antara lain Basecamp, pos, shelter, titik mata air, titik situs di sepanjang jalur, puncak, jarak, dan estimasi waktu tempuh. Peta tersebut dapat diakses secara offline untuk navigasi dan pelacakan lokasi. Peta digital ini memudahkan pendaki dalam navigasi dan perencanaan, mengurangi risiko kecelakaan selama kegiatan mendaki gunung.